Modelling migration process of long-lived radionuclides from graphite radioactive waste - Alexander Olegovich Pavlyuk; Sergey Gennadievich Kotlyarevskiy; Evgeniy Vladimirovich Bespala; Anna Genrikhovna Volkova; Elena Vasilievna Zakharova; Nataliya Dmitrievna Andryushchenko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
The relevance of the discussed issue is caused by the need to identify the properties of engineering clay safety barriers that characterize the reliability of isolation of long-lived radionuclides at the place of disposal of graphite solid radioactive waste. The main aim of the study is to assess the effect of parameters variation, which characterize protective properties of material, on the dynamics of propagation of long-lived radionuclides 14C and 36Cl from the repository of graphite radioactive waste. The methods used in the study: mathematical modeling of the migration process of long-lived radionuclides taking into account diffusion and filtration flows by solving the quasi-one-dimensional nonstationary diffusion equation in the Mathlab software complex. The results. The authors have developed the mathematical model of migration of long-lived radionuclides from irradiated graphite of uranium-graphite reactors in storage to clay safety barriers that takes into account the filtration movement of moisture and reduction of radionuclide activity due to radioactive decay. It was shown that the diffusion fluxes of radionuclides in natural clays are insignificant and have practically no effect on migration. The most significant factor is the forced convection when moving moisture. As a result, radionuclides are transported through safety barriers to host rocks. It was proved that the clay-containing safety barriers currently used reliably isolate the radionuclide 14C at the point of conservation or disposal of irradiated nuclear graphite even in the event of their watering. At the same time, the non-intervention level for 36Cl in such a safety barrier is possible only if there are no convective moisture flows for the considered conservative modeling conditions. For a real repository, the condition of non-intervention of the level of interference for 36Cl is determined by significantly lower activity of 36Cl compared to 14C, and also by multiple dilution of the 36Cl concentration as far as the distance from the source of the final geometry was shown in the article.